Handbook of plastic foams : types, properties, manufacture, and applications - Landrock, Arthur H. (Noyes Publications, 1995)
This book is a source of information on plastic foams (cellular plastics), including structural plastic foams. Elastomer (rubber-like) foams are also considered. The book is for those who require a non-theoretical handbook in the subject area. It should be applicable to materials engineers, plastics fabricators, chemists, chemical engineers, and students.
Keywords: Plastic foams.; elektronické knihy; electronic books